2020
DOI: 10.1093/jjco/hyaa027
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in Japanese patients with prostate cancer following proton beam therapy: an institutional cohort study

Abstract: Objective Many treatment options have guaranteed long-term survival in patients with localized prostate cancer and health-related quality of life has become a greater concern for those patients. The purpose of this study was to reveal the health-related quality of life after proton beam therapy and to clarify the differences from other treatment modalities for prostate cancer. Methods Between January 2011 and April 2016, 583 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…In one study sexual summary score declined significantly from baseline to 5 years follow-up (67 to 53) in patients not receiving ADT (20) and remained low and stable in patients receiving ADT. Another study revealed a significantly poorer urinary obstruction/irritation score at the end of treatment compared to baseline, but recovering afterwards (27), the same pattern was seen in one of the other publications using EPIC-26 for PROs (31).…”
Section: Disease Free Biochemical Survival and Overall Survivalsupporting
confidence: 66%
“…In one study sexual summary score declined significantly from baseline to 5 years follow-up (67 to 53) in patients not receiving ADT (20) and remained low and stable in patients receiving ADT. Another study revealed a significantly poorer urinary obstruction/irritation score at the end of treatment compared to baseline, but recovering afterwards (27), the same pattern was seen in one of the other publications using EPIC-26 for PROs (31).…”
Section: Disease Free Biochemical Survival and Overall Survivalsupporting
confidence: 66%